Antimicrobial sensitivity profile of isolated bacteria, from piometra in bitches, in front of uterine infusion gentamycin (Gentrin®) (Research, Society and Development, 2021)
The hyperplastic cystic endometrial - pyometra complex is characterized by a hormonal disorder, with progesterone as the protagonist, leading to the appearance of ovarian cysts and a sequence of changes in the endometrium, followed by bacterial colonization, with Escherichia and Staphylococus being among the main ones, being thus, the objective was to isolate them and evaluate their sensitivity to Gentrin® in three different concentrations (150mg, 200mg and 300mg), with Ceftriaxone as control. Ten female dogs were used for this research, with an average age of 7 years, after collecting the secretions of pyometra, Escherichia and Staphylococus were isolated from them for culture and antibiogram. They were isolated from E. coli in 60% of the samples and Staphylococus spp. in 40%, in the antibiogram tests both demonstrated 100% sensitivity to Gentrin® of 300mg, and in smaller percentages to 150mg and 200mg. This concludes the effectiveness of Gentrin® 300mg in the treatment by uterine infusion for pyometra.